Community empowerment in implementing effleurage massage for women in labor at pratama deliana clinic - Juli Selvi Yanti; Eka Maya Saputri; Khairunnisa; Alda Musdalifah (Peneliti Teknologi Teknik Indonesia, 2022)
Effleurage massage is one of the massage methods to reduce pain during labor which is listed in the Summary of pain relief measures during labor, where during the first stage of the latent phase (0-3 cm opening) and the active phase (4-7 cm opening) the activity that can be carried out by labor mothers is effleurage. Effleurage is light massage using your fingers, usually on your stomach, in rhythm with your breathing during contractions. Effleurage can be done by the birthing mother herself or by the birth attendant during the contractions. The purpose of this community service is to increase the knowledge of birthing mothers and their families about Effleurage massage. The results of the community service carried out on 15 mothers who gave birth found that the majority of mothers were 80% able to overcome/manage the pain they felt. It is hoped that this service activity can be continued starting when the mother is pregnant so that the mother is not confused in carrying out effleurage massage during childbirth.